Primary production in wild and cultivated cranberries - (:unkn) unknown (My University, 1980)
Cranberries grow in many Wisconsin sphagnum bogs. One of the two species, the large cranberry, Vaccinium macrocarpon Alt., is among the few American fruit crops in cultivation. Most of the cultivated cranberries have been derived by selection from wild, and more recently from cultivated clones. Like the large cranberry, the small cranberry, Vaccinium oxycoccos L., is native to Wisconsin bogs and it, too, provides wildlife food, though it has not been selected for cultivation. This study examined the primary productivity of wild and cultivated cranberries (Wahlstrom 1979).
Keywords: cranberries; productivity